2004
DOI: 10.1037/0022-006x.72.6.1073
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Neuropsychological Recovery in Clients With Alcohol Use Disorders Who Were Exposed to Different Treatments.

Abstract: Risk covariates of neuropsychological ability (NA) at treatment entry and neuropsychological recovery (NR) across 15 months were examined and replicated in 2 samples (Ns = 952 and 774) from Project MATCH, a multisite study of alcoholism treatments. NA at treatment entry was associated with age, education, and other covariates. Statistically significant mean increases in NA over time had small effect sizes, suggesting limited clinical significance of NR in the samples as a whole. However, initial NA and a combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…Further, studies with larger samples have shown that familial alcoholism, antisocial personality, and physical well-being, all perhaps phenotypes for a more basic genetic trait, as well as age and education, can all predict level of neuropsychological deficits (Grant et al, 1984;Tarter and Edwards, 1986;Parsons, 1987b;Bates et al, 2002;Bates et al, 2005). Our study, however, does not have the power (cf, Bates et al, 2004) to determine whether such variables contributed to the Relapsers' initial superior performance.…”
Section: Discussionmentioning
confidence: 68%
“…Further, studies with larger samples have shown that familial alcoholism, antisocial personality, and physical well-being, all perhaps phenotypes for a more basic genetic trait, as well as age and education, can all predict level of neuropsychological deficits (Grant et al, 1984;Tarter and Edwards, 1986;Parsons, 1987b;Bates et al, 2002;Bates et al, 2005). Our study, however, does not have the power (cf, Bates et al, 2004) to determine whether such variables contributed to the Relapsers' initial superior performance.…”
Section: Discussionmentioning
confidence: 68%
“…Deficits in EFs are proposed as important mediators in drug bingeing [15], and several studies suggest that impairments in EFs have a negative impact on treatment success and relapse in substance dependence [100][101][102][103]. The EF deficits as found in PG as well as AD in this study may therefore foster the continuation of these disorders, limit the impact of psychosocial treatment and promote relapse after discontinuation of PG or AD.…”
Section: Discussionmentioning
confidence: 74%
“…Living close to a gambling establishment in combination with being disinhibited could lead to a diminished ability to inhibit the urge to enter a gambling establishment. Studies on relapse in patients with substance use disorders indeed indicate that neurocognitive abilities interact with intrapersonal and environmental factors in the prediction of relapse (Tapert et al 1999 ;Latimer et al 2000 ;Bauer, 2001 ;Bates et al 2004). Therefore, it is likely that interactions between neurocognitive deficits and factors such as coping skills, gambling behavior of relatives and friends, and proximity to gambling opportunities influence relapse in PG in a similar way.…”
Section: Discussionmentioning
confidence: 99%